10.1371/journal.pmed.0020297 (CrossRef Listing of Deleted DOIs, 2000)
While the emphasis on strengthening and utilising a unified national system has gained momentum in discussions among health partners throughout the world, there are evident discrepancies between commitments and practice. Sudan presents an interesting case where the last decade has witnessed major political changes that have influenced health sector partnerships. This study investigates the shifts in attitudes and practices of Sudan's health sector partners towards strengthening and utilising the national health system, specifically focusing on the components of financial management, procurement and supply, and health information. Utilising a qualitative case study design, data were collected through semi-structured interviews with key stakeholders from various humanitarian and developmental partners during two rounds (2015 and 2021/22). The interviews were analysed thematically, and situational analysis was applied with the partners' stances displayed on positional maps. The findings revealed a shift from initial resistance to and prevention of system strengthening and utilisation to a more collaborative approach towards the system utilisation, influenced by political changes, and the need to adopt resilient approaches to respond to the volatile emergency context. Meanwhile, over time humanitarian partners have persisted to utilise their own systems because they have control over these systems or believe their systems function better. Moreovere, some respondents claimed that they are not mandated to support a unified system. Tension persists between utilising the system as prerequisite to strengthen it or ensuring the system is strengthened before using it. The study highlights the critical need for continuous monitoring and commitment to utilising the national system by all to ensure sustainability and enable timely improvement, especially in fragile contexts like Sudan. Flexible arrangements and guidance to encourage humanitarian partners to commit to abolishing parallel systems are crucial.